2018
DOI: 10.1097/cmr.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of anti-PD-1 therapy for metastatic melanoma and non-small-cell lung cancer in patients with viral hepatitis: a case series

Abstract: Anti-PD-1 monoclonal antibodies have shown durable long-term survival benefit in patients with metastatic melanoma. Limited evidence exists on the safety and efficacy of PD-1 inhibitors in patients with hepatitis B virus (HBV) and hepatitis C virus (HCV) infections as these patients have traditionally been excluded from clinical trials because of a theoretical risk of immune reconstitution inflammatory syndrome. We aim to determine the safety and efficacy of treatment with PD-1 inhibitors in seven patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…In another study, anti‐PD‐1 therapy induced disease flares in 38% of melanoma patients with autoimmune disease, and 12% of patients discontinued ICI treatment because of underlying disease flares or irAEs . Another study investigating anti‐PD‐1 therapy for seven melanoma or NSCLC patients with viral hepatitis revealed that one HCV patient experienced grade 2 ALT elevation and four patients experienced grade 1 ALT elevation . Regarding ILD, a case series indicated that anti‐PD‐1‐related pneumonitis occurred more frequently in NSCLC patients with ILD than in those without (31% vs 12%, P = .014) .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, anti‐PD‐1 therapy induced disease flares in 38% of melanoma patients with autoimmune disease, and 12% of patients discontinued ICI treatment because of underlying disease flares or irAEs . Another study investigating anti‐PD‐1 therapy for seven melanoma or NSCLC patients with viral hepatitis revealed that one HCV patient experienced grade 2 ALT elevation and four patients experienced grade 1 ALT elevation . Regarding ILD, a case series indicated that anti‐PD‐1‐related pneumonitis occurred more frequently in NSCLC patients with ILD than in those without (31% vs 12%, P = .014) .…”
Section: Introductionmentioning
confidence: 99%
“…For patients who have positive screening test results, chest imaging may be performed. Further evaluation for TB may be carried out for patients with abnormal chest imaging results. Recent studies indicate that PD‐1/PD‐L1 inhibitors do not show increased toxicity in patients with tumor in the context of hepatitis B virus (HBV) or hepatitis C virus (HCV) infection . However, for patients developing irAEs, treatment with immunosuppressive therapy may increase the risk of reactivation of HBV/HCV infection.…”
Section: Diagnosismentioning
confidence: 99%
“…26 Therefore, further studies are needed to investigate the relationship between PD-1/PD-L1 blockage and infection. 27,28 However, for patients developing irAEs, treatment with immunosuppressive therapy may increase the risk of reactivation of HBV/HCV infection. Furthermore, for patients without irAEs or treatment with immunosuppressants, there is a possibility of reactivation of latent/chronic infections following immune checkpoint inhibitor therapy.…”
Section: Clinical Data Review and Description Of Potential Mechanism mentioning
confidence: 99%
“…Good safety profiles for patients with hepatitis C have already been reported for anti-PD-1 therapy [12,13]. Therefore, careful clinical examination and a detailed anamnesis is of great importance.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Therefore, careful clinical examination and a detailed anamnesis is of great importance. Good safety profiles for patients with hepatitis C have already been reported for anti-PD-1 therapy [12,13]. Serial application of the anti-PD-1 mAb nivolumab and ledipasvir has also been described in a patient with advanced melanoma and hepatitis C [14].…”
Section: Dear Editorsmentioning
confidence: 99%